2021
DOI: 10.1016/j.isci.2020.101890
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning in plant science and plant breeding

Abstract: Summary Technological developments have revolutionized measurements on plant genotypes and phenotypes, leading to routine production of large, complex data sets. This has led to increased efforts to extract meaning from these measurements and to integrate various data sets. Concurrently, machine learning has rapidly evolved and is now widely applied in science in general and in plant genotyping and phenotyping in particular. Here, we review the application of machine learning in the context of plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
130
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(131 citation statements)
references
References 99 publications
0
130
0
1
Order By: Relevance
“…The ability to use these large collections of reflectance-based information increases the chances of finding meaningful signals which contribute to a better interpretation of the data, allowing for the development of more accurate prediction models. To date, several machine learning algorithms have been used to analyze and understand plant spectral data [18][19][20], however, there is no standard consensus on the best technique to use as this depends on a number of factors, such as the type of problem, type and size of the data, and type of output, for example. Therefore, a comparative approach is a conventional method to assess an algorithm's suitability to solve a particular problem.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to use these large collections of reflectance-based information increases the chances of finding meaningful signals which contribute to a better interpretation of the data, allowing for the development of more accurate prediction models. To date, several machine learning algorithms have been used to analyze and understand plant spectral data [18][19][20], however, there is no standard consensus on the best technique to use as this depends on a number of factors, such as the type of problem, type and size of the data, and type of output, for example. Therefore, a comparative approach is a conventional method to assess an algorithm's suitability to solve a particular problem.…”
Section: Introductionmentioning
confidence: 99%
“…This study identified greater allelic diversity in wild soybean and a set of 205,614 SNPs for use in quantitative trait loci (QTL) mapping and association studies. Very recently, Valliyodan et al (2021) analyzed genetic diversity and structure from the resequencing of 481 diverse soybean accessions, comprising 52 wild selections and 429 cultivated varieties (landraces and elites). This study identified evidence of distinct, mostly independent selection of lineages by particular geographic location.…”
Section: Genome Sequencing and Resequencingmentioning
confidence: 99%
“…Hence, the concept of an automated plant disease detection system was proposed [40]. Machine learning has been utilized to analyze and classify the input data for automatically detecting plant disease [41]- [43]. In terms of Ganoderma disease of oil palm, remote sensors with quantifiable input data are utilized and paired with machine learning approaches.…”
Section: Machine Learning For Ganoderma Disease Detectionmentioning
confidence: 99%